Research on aerodynamic drag reduction for 400 km/h high-speed trains - Wang, Tiantian; Yang, Li; Wang, Yu; Liu, Hongkang; Zhang, Lei (Advances in Wind Engineering, 2025)
To improve the transportation efficiency, the trains are designed for higher operational speed. When the train speed increases, its aerodynamic drag grows dramatically and the operational energy consumption surges. Throughout the world, current high-speed trains (HSTs) run at a maximum speed of 350 km/h in commercial operations, and higher-speed trains are expected to reach 400 km/h. To reduce the energy consumption of 400 km/h HSTs from the aerodynamic perspective, it is urgent to investigate its aerodynamic drag characteristics and to propose drag reduction schemes with application value. In this paper, the aerodynamic characteristics of a 400 km/h HST were analyzed using numerical simulation methods. The drag reduction designs were proposed and evaluated. The results showed that for a HST running at 400 km/h, the aerodynamic drag accounted for a larger proportion in the areas of train head, pantograph and bogie. The total drag can be changed by different streamlined lengths, train heights, depths of pantograph platforms, pantograph structures, bogie fairing and bottom plates. After coupling the drag reduction schemes for each area, the aerodynamic drag was reduced by up to 22.11% compared to the original model. This paper provides ideas for the study of drag reduction for HSTs. The proposed drag reduction measures can guide the engineering design of aerodynamic shapes for higher-speed trains.